Analysis Relationship Between Job Embeddedness And Organizational Citizenship Behavior (OCB) In Ulamm Employees PT. Makassar Branch Civil National Capital - Ziaul Haq; Sumardi Sumardi; Jusni Jusni (Program Pascasarjana STIE Amkop Makassar, 2023)
OCB behavior is behavior related to work, is spontaneous, voluntary, sometimes not obvious, is outside the specified role description, and may contribute more to the performance of colleagues or superiors. This behavior is also not in the system of rewards or punishments (reward and punishment) formally. This behavior cannot be forced to be owned by every employee because there are no sanctions that will be imposed if they do not have OCB. Therefore, it is difficult for organizations to require their employees to have formal OCB, even though the emergence of this behavior is highly expected by every organization. Organizations can only try to create a conducive environment to spur the emergence of OCB. One of the factors suspected of causing OCB behavior is job embeddedness. Job embeddedness is an employee's sense of compatibility with the company where he works. This research wants to know the relationship between OCB and job embeddedness in UlaMM employees of PT PNM Makassar Branch. From the results of the correlation analysis it can be concluded that there is a positive and significant effect of job embeddedness dimensions of Fit and Sacrifice on OCB. This means that the higher the value of job embeddedness, the higher the OCB value. Keywords: Job embeddedness,Organizational Citizenship Behavior.